ABOUT NETWORKS PES16–4, PES16–2 AND PES16–1, CREATED ON THE BASIS NETWORK PES16–8 - Туйчиев, Гулом Нумонович (Ukrainian Information Security Research Journal, 2015)
In the paper on the basis of the network PES16–8 developednetworks PES16–4, PES16–2 and PES16–1 consistingof four, two, and one round function. The main advantageof the proposed network that during encryptionand decryption using the same algorithm as well as around function can be any transformation. In the networkPES16-8 length of subblock is 8, 16 and 32 bits and basison the network can create the encryption algorithm alength of subblock 128, 256 and 512 bits. In a networkPES16-8 algebraic operations are variable, as these operationscan use the operations of addition and multiplicationmodulo and XOR.